Satellite perspectives on the spatial patterns of new snowfall in the Southern Appalachian Mountains. Issue 16 (3rd April 2014) - Sugg, Johnathan W.; Perry, L. Baker; Hall, Dorothy K.; Riggs, George A.; Badurek, Christopher A.; Pelto, Mauri; Kelly, Richard
Abstract The Southern Appalachian Mountains (SAM) are a heavily forested mid‐latitude mountain region that provide an ideal location for assessing the suitability of satellite‐derived snow maps and explicitly linking atmospheric circulation to the spatial patterns of new snowfall. Although a variety of synoptic‐scale circulation regimes contribute to mean annual snowfall, which ranges from roughly 25 cm in the lowest valleys to over 250 cm at the highest elevations, atmospheric circulation processes have largely been absent from efforts seeking to quantify the spatial patterns of new snowfall. In this paper, we examine the suitability of fractional snow cover (FSC) maps from the Moderate Resolution Imaging Spectroradiometer (MODIS) and determine the spatial extent of snowfall according to synoptic‐scale circulation. FSC maps are analysed after 122 snow events from 2006 to 2012 to provide a suitability analysis of MODIS products for use in the SAM. For each event, we calculate FSC distribution and total snow‐covered area and compare it with available in situ observations. Results indicate that the SAM presents unique meteorological, physical, and spectral characteristics that are ideal for evaluating the suitability of MODIS for measuring snow cover. Out of 122 observed snow events, 63 are considered suitable for analysis with the FSC maps. The highest FSC values are observed after Gulf/Atlantic lows and south‐eastward tracking clipper systems. We conclude that MODIS data can be successfully used to link broader atmospheric circulation processes of snowfall with the spatial patterns of snow cover. Copyright © 2014 John Wiley & Sons, Ltd.